Analisis Tegangan Regangan dan Defleksi pada Sambungan Balok-Kolom Beton Bertulang Menggunakan Beban Statik - Prayuda, Hakas; Cahyati, Martyana Dwi; Soebandono, Bagus (MEDIA KOMUNIKASI TEKNIK SIPIL, 2018)
Reinforced concrete is commonly used in any infrastructures. In building, it can be applied for beam and column separately, but the joints between those elements in this type of structure might be vulnerable due to the strength compared to the element itselft. In this study, some parameters namely ductility, stiffness, and energy dissipation of beam-column connection in precast concrete will be examined using finite element method. Six samples in this experiment are made considering some variations such as connection type in interior and exterios condition, round-shaped and rectanguler-shaped of column, and T-shaped and rectanguler-shaped of beam. Static loads were given in the middle of the beam and column so that the crack pattern can be obtained. From this experiment, it will be known the best and suitable joints by observing those three parmeters.